Characteristics of pyridine adsorption on Au(111) and Au(210) by EIS parameters fitting procedure - Motheo, Artur de Jesus; Saldanha, Rosangela Maria Pompônio; Neves, Rodrigo de Santis; de Robertis, Eveline; Sadkowski, Andrzej (Eclética Química, 2003)
Some aspects of the application of electrochemical impedance spectroscopy to studies of solid electrode / solution interface, in the absence of faradaic processes, are analysed. In order to perform this analysis, gold electrodes with (111) and (210) crystallographic orientations in an aqueous solution containing 10 mmol dm -3 KF, as supporting electrolyte, and a pyridine concentration varying from 0.01 to 4.6 mmol dm -3 , were used. The experimental data was analysed by using EQUIVCRT software, which utilises non-linear least squares routines, attributing to the solid electrode / solution interface behaviour described by an equivalent circuit with a resistance in series with a constant phase element. The results of this fitting procedure were analysed by the dependence on the electrode potential on two parameters: the pre-exponential factor, Y 0 , and the exponent n f , related with the phase angle shift. By this analysis it was possible to observe that the pyridine adsorption is strongly affected by the crystallographic orientation of the electrode surface and that the extent of deviation from ideal capacitive behaviour is mainly of interfacial origin.